The financial health of the US farm sector - Belasco, Eric J.; Glauber, Joseph W. (American Enterprise Institute, 2022)
Key Points After a relatively short period when the agricultural sector experienced close-to-average farm incomes, net farm incomes increased well above their 20-year inflation-adjusted averages in 2020 and 2021 because of federal emergency relief payments and relatively high agricultural commodity prices. Farm incomes are forecasted to remain well above average levels in 2022, despite the rollback of pandemic-related subsidies and rising costs for major farm inputs, because prices received by farmers for many commodities have been exceptionally high. While trade wars, widespread drought, high input prices, and volatile international markets have created challenges for US agriculture, the farm sector as a whole, and the vast majority of farms, is in an exceptionally healthy financial position as Congress begins to consider the provisions of the 2023 Farm Bill.